2021
DOI: 10.1051/e3sconf/202131901057
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of the imported Malaria in the north region of Morocco from 2014 to 2018

Abstract: In Morocco, the epidemiological surveillance of imported Malaria still be the pillar of the eradication strategy of the disease as part of environmental health. The aim of this study is to describe the epidemiological profile of malaria in north region of Morocco. It is retrospective descriptive study, based on program reports, carried out from 28 April 2019 to 18 February 2020 covering 2014-2018 period. The statistical analysis is performed by Epiinfo 7. In total, 59 cases of imported Malaria were reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…[4][5][6] Having actively adhered to international initiatives (Roll Back Malaria), the country succeeded in gradually reducing the number of indigenous cases to 19, 4, and 1 in 2002, 2003, and 2004, respectively, reaching a total cessation of transmission in 2005. 7 This enabled the World Health Organization to certify it as a malaria-free country in May 2010, 3 while strongly recommending maintaining appropriate antimalarial programmes to prevent its possible re-emergence. Several factors contributed to this accomplishment (i.e., the decline of malaria), encompassing alterations in land use and agriculture, advancements in socioeconomic conditions, and dedicated intervention initiatives.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[4][5][6] Having actively adhered to international initiatives (Roll Back Malaria), the country succeeded in gradually reducing the number of indigenous cases to 19, 4, and 1 in 2002, 2003, and 2004, respectively, reaching a total cessation of transmission in 2005. 7 This enabled the World Health Organization to certify it as a malaria-free country in May 2010, 3 while strongly recommending maintaining appropriate antimalarial programmes to prevent its possible re-emergence. Several factors contributed to this accomplishment (i.e., the decline of malaria), encompassing alterations in land use and agriculture, advancements in socioeconomic conditions, and dedicated intervention initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…8 In 2017 alone, the Moroccan health ministry registered 291 imported malaria cases, with an average of 255.60 cases per year between 2012 and 2016. 7 The majority were adults and males returning from endemic areas, especially African countries. Another retrospective descriptive study carried out in the north part of the country from 2014 to 2018 reported 59 cases of imported Malaria, of which 55% and 25.9% were from Guinea and Ivory Coast.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations